1968
DOI: 10.3181/00379727-129-33366
|View full text |Cite
|
Sign up to set email alerts
|

Production of Antibodies against Insecticide-Protein Conjugates

Abstract: sine, phenylalanine, and ornithine. In this connection it is interesting to note that the average weight of the liver between 150 and 175 days only increased 1.3%. An increase in free amino acid concentration during this period could be explained by a general increase in metabolic activity and enzyme maturation. A decrease in concentrations of the TCA cycle related amino acids, glutamic acid and aspartic acid, may be related to the sharp increase in demand for energy, but no proof is available. Correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Most work has been done on immunoassays for herbicides, but some work on the organophosphorus pesticides parathion (Ercegovich et al, 1981;Heldman et al, 1985;Ngeh-Ngwainbi et al, 1986) and malathion (Haas and Guardia, 1968;Centeno et al, 1970) and the organophosphorus nerve gas soman (Hunter et al, 1982;Buenafe and Rittenberg, 1987) has been reported. In this paper, the development of specific polyclonal and * Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Most work has been done on immunoassays for herbicides, but some work on the organophosphorus pesticides parathion (Ercegovich et al, 1981;Heldman et al, 1985;Ngeh-Ngwainbi et al, 1986) and malathion (Haas and Guardia, 1968;Centeno et al, 1970) and the organophosphorus nerve gas soman (Hunter et al, 1982;Buenafe and Rittenberg, 1987) has been reported. In this paper, the development of specific polyclonal and * Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 96%
“…Over the past few years, enzyme-linked immunosorbent assay (ELISA) methods have been developed as attractive options for either the identification or quantification of a variety of agrochemicals in water, soil, and, in some cases, agricultural produce (Hammock et al, 1987;Jung et al, 1989). Most work has been done on immunoassays for herbicides, but some work on the organophosphorus pesticides parathion (Ercegovich et al, 1981;Heldman et al, 1985;Ngeh-Ngwainbi et al, 1986) and malathion (Haas and Guardia, 1968;Centeno et al, 1970) and the organophosphorus nerve gas soman (Hunter et al, 1982; Buenafe and Rittenberg, 1987) has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts to obtain antibodies for DDT and related compounds have been previously carried out. immunogens resulted in low-affinity antisera that mainly recognized DDA, the chief urinary metabolite of DDT (Haas and Guardia, 1968;Centeno et al, 1970;Furuya and Urasawa, 1981;Banerjee, 1987). Further work by Bu ¨rgisser et al (1990) using a new immunogenic dicofolderived hapten allowed them to obtain a monoclonal antibody (MAb) to DDT that exhibited an I 50 around 100 nM in a competitive solid-phase radioimmunoassay.…”
Section: Introductionmentioning
confidence: 99%
“…From a panel of possible antibod- ies and enzyme-labeled hapten combinations, five assays were selected and evaluated for application to food and environmental matrices. Other immunoassays have been developed for DDA (Haas and Guardia, 1968;Centero et al, 1970;Furuya and Urasawa, 1981), although much of this work predated the development of sensitive nonisotopic methods, such as the ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…While maintaining comparable sensitivity, they are simple and cost-effective and can be adapted for field use (Gee et al, 1995;Lee et al, 1995). Earlier, several groups have attempted to develop antibodies for detection of DDT and metabolites by forming esters or amides of DDA (Haas and Guardia, 1968;Centero et al, 1970;Furuya and Urasawa, 1981;Banerjee, 1987); however, typically these antibodies detected DDT much more poorly than they did DDA. Burgisser et al (1990) designed a hapten based on dicofol, which, unlike the DDA-derived haptens, retained the -CCl 3 moiety of DDT, and developed a competitive radioimmunoassay of low to moderate sensitivity.…”
Section: Introductionmentioning
confidence: 99%